Successful Correction of Crossbite with Multi-Segment Le Fort I Osteotomy in a Patient with Cleft Lip and Palate - Naoko Nemoto; Hitoshi Kawanabe; Akihiko Oyama (Dentistry Journal)
Objectives: Cleft lip and palate is a multifactorial disease that causes various problems, such as maxillary and facial morphological abnormalities, oral dysfunction, and postoperative scarring due to lip and palate formation after birth. This condition can easily cause obstruction and may require surgical orthodontic treatment in the future. Methods: In this study, we performed multi-segment Le Fort type 1 osteotomy on a patient with a cleft lip and palate who presented with a crossbite, horizontal inclination of the occlusal plane due to dental arch stenosis on the left side of the maxilla, and deviation of the mandible. Results: In this case, close occlusion was achieved by improving the patient’s facial appearance and occlusal relationship by combining sagittal division of the mandibular ramus, and the stability of the occlusion was measured without relapse 1 year after the surgery. Conclusions: This case is considered of great medical significance, as there have been few reports of cases showing a stable course.